2017
DOI: 10.3389/fphar.2017.00258
|View full text |Cite
|
Sign up to set email alerts
|

How General Practitioners and Their Patients Adhere to Osteoporosis Management: A Follow-Up Survey among Czech General Practitioners

Abstract: Introduction: General practitioners (GPs) are key participants in osteoporosis (OP) management. The aim was to evaluate their adherence to lege artis management of the disease, potential barriers, and to discuss differences observed in comparison with the baseline survey carried out in 2007; the focus was on secondary prevention.Methods: On behalf of two professional associations, 2-round postal survey among randomly selected GPs (>1/4 of all Czech GPs) was performed in 2014. The questionnaire covered areas co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 18 publications
5
18
1
Order By: Relevance
“…Only 40.3% of those with indications for treatment received BPs and 47.9% with calcium and vitamin D. In our study, about two-thirds of all treated patients received proper supplementation. A follow-up survey among Czech GPs revealed that only 60% of the respondents were adherent to the guidelines [ 15 ]. Calcium supplementation was started by 41% of the respondents and vitamin D by 40% only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 40.3% of those with indications for treatment received BPs and 47.9% with calcium and vitamin D. In our study, about two-thirds of all treated patients received proper supplementation. A follow-up survey among Czech GPs revealed that only 60% of the respondents were adherent to the guidelines [ 15 ]. Calcium supplementation was started by 41% of the respondents and vitamin D by 40% only.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium supplementation was started by 41% of the respondents and vitamin D by 40% only. This study focused attention to the lack of possibility to prescribe selected drugs (in 61%) and the financial limits introduced by the health insurance authorities (44%) [ 15 ]. All of this increased the financial burden on the patient in addition to the low willingness of patients to pay for drugs out of pocket [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the key studies identified by the researcher (Blazkova et al, 2010;Chami et al, 2006;Khan et al, 2013;Vytrisalova et al, 2014;Vytrisalova et al, 2017) this study's results should be relatable to future comparable studies. Statistical input and advice were sought regularly throughout this research undertaking.…”
Section: Discussionmentioning
confidence: 74%
“…Unfortunately, no responses were received despite polite follow up email messages. The [36] survey tool utilised for this study was therefore, constructed by utilising the answers described in the relevant research studies for retrospective extrapolation of the answers, stemming from questions that were likely asked, see (Blazkova et al, 2010;Chami et al, 2006;Khan, Mallhi, Sarriff, & Khan, 2013;Vytrisalova et al, 2014;Vytrisalova et al, 2017).…”
Section: Survey Tool Validitymentioning
confidence: 99%